APOE‐ε4 allele for the diagnosis of Alzheimer's and other dementia disorders in people with mild cognitive impairment in a community setting - Elias‐Sonnenschein, Lyzel S (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows: Our primary objective is to determine the diagnostic accuracy of the APOE‐ε4 allele in detecting AD dementia and other types of dementia in people with MCI in a community setting.